A population-based cohort study of mitochondrial disease and mental health conditions in Ontario, Canada - Laura C. Rosella; Mackenzie Hurst; Emmalin Buajitti; Thomas Samson; L. Trevor Young; Ana C. Andreazza (Orphanet Journal of Rare Diseases)
Abstract Background Mitochondrial disease has been linked to mental health disorder in clinical cohorts and post-mortem studies. However, a lack of population-level studies examining the relationship between mitochondrial disease and mental health has resulted in an evidence gap and creates a challenge for identifying and addressing care needs for the mitochondrial disease population. Using multiple linked population health databases in a single-payer health system that covers the full population, this study aimed to investigate the prevalence of mood disorders and other mental health conditions in patients with mitochondrial disease and to examine the joint impact of mitochondrial disease and mental health conditions on healthcare use and health system costs. To contextualize these findings, a clinical comparator cohort of multiple sclerosis (MS) patients was analyzed. Results Overall, co-prevalent mental health conditions are common in the mitochondrial population. Double the proportion of patients in the mitochondrial disease cohort had a co-prevalent mental health illness as compared to the MS population (18% vs 9%). Healthcare utilization was highest among patients with co-prevalent mitochondrial disease and mental illness, with 49% hospitalized within 1 year prior to cohort entry (compared to 12% of MS patients with no mental health condition). Costs were likewise highest among mitochondrial disease patients with mental health conditions. Conclusions This study presents the first comprehensive, population-wide cohort study of mitochondrial disease and co-prevalent mental health conditions. Our findings demonstrate a high burden of mental health conditions among mitochondrial disease patients, with high associated health care needs. We also find that patients with concurrent mental illness and mitochondrial disease represent a high-burden, high-cost population in a single-payer health insurance setting.